Role of Workplace Bullying in Self-determination Needs among University Teachers - Vishwakarma, Amit Kumar; Kumari, Pushpa; Vishwakarma, Babita (Indian Journal of Extension Education, 2024)
Workplace bullying is a pervasive issue that significantly affects the professional performance of university teachers. This research explores the relationship between workplace bullying and the fulfilment of self-determination needs specifically autonomy, competence, and relatedness among university faculty. The study’s sample comprised 333 faculty members from the University of Varanasi, Uttar Pradesh, India. Data were collected during 2023 using the Negative Act Questionnaire-Revised (NAQ-R) to assess workplace bullying and the Intrinsic Need Satisfaction Scale (INS) to measure self-determination needs. Before analysis, the basic assumptions of statistical methods were verified. The data were then analyzed using descriptive statistics, Pearson’s product-moment correlation, and simple linear regression (SLR) through SPSS. The findings revealed a significant negative correlation between workplace bullying and the satisfaction of self-determination needs at a 0.001 significance level. Additionally, workplace bullying was identified as a significant predictor, accounting for an 8 per cent variance in self-determination needs. In conclusion, workplace bullying undermines intrinsic motivational needs-autonomy, competence, and relatedness. The study also discusses limitations and suggests future directions to improve the work environment.
Keywords: Workplace bullying; Self determination needs; Autonomy; Competence; Relatedness